Credo ut Intelligam: Relevansi Pemikiran Agustinus bagi Krisis Iman di Era Modern - Fransiskus Jonpaul Jorgin Kewa Kebu; Fransiskus Vitores; Alvianus Mayon Sukardi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the relevance of the thought of Augustine of Hippo, particularly the concept of credo ut intelligam (“I believe so that I may understand”), in addressing the crisis of faith in the modern era. The background of this research is rooted in the tendency of modern society to prioritize reason while neglecting faith, leading to skepticism, relativism, spiritual emptiness, and the loss of existential meaning in human life. These conditions cause many individuals to lose their sense of direction, moral foundation, and spiritual relationship with God. The purpose of this study is to analyze how Augustine’s thought can function as a bridge between faith and reason within the context of contemporary life. This research employs a qualitative method using philosophical and hermeneutical approaches through the study of Augustine’s writings and other supporting literature. The findings reveal that Augustine did not reject reason; instead, he regarded faith as the foundation that enlightens human reason in attaining truth and genuine knowledge. Therefore, his thought remains relevant as a philosophical and spiritual guide for overcoming crises of meaning, morality, and faith in modern society.